Mechanism of seizure-induced retrograde amnesia. (May 2021) - Naik, Aijaz Ahmad; Sun, Huayu; Williams, Cedric L.; Weller, Daniel S.; Julius Zhu, J.; Kapur, Jaideep
Highlights: A single seizure caused transient retrograde amnesia. Learning and seizure activated CA1 hippocampal neuronal ensembles overlapped. Seizure potentiated CA1 neuron synapses such that further LTP did not occur. Seizures hijack memory mechanisms to interfere with storage and retrieval. Abstract: Seizures cause retrograde amnesia, but underlying mechanisms are poorly understood. We tested whether seizure activated neuronal circuits overlap with spatial memory engram and whether seizures saturate LTP in engram cells. A seizure caused retrograde amnesia for spatial memory task. Spatial learning and a seizure caused cFos expression and synaptic plasticity overlapping set of neurons in the CA1 of the hippocampus. Recordings from learning-labeled CA1 pyramidal neurons showed potentiated synapses. Seizure-tagged neurons were also more excitable with larger rectifying excitatory postsynaptic currents than surrounding unlabeled neurons. These neurons had enlarged dendritic spines and saturated LTP. A seizure immediately after learning, reset the memory engram. Seizures cause retrograde amnesia through shared ensembles and mechanisms.